1999
DOI: 10.1017/s0029665199000361
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional adequacy of plant-based diets

Abstract: fax +44 (0)171 333 4273, email Tom. Sanders@kcl.ac.uk The nutritional adequacy of plant-based diets is discussed. Energy and protein intakes are similar for plant-based diets compared with those containing meat. Fe and vitamin B 12 are the nutrients most likely to be found lacking in such diets. Bioactive substances present in foods of plant origin significantly influence the bioavailability of minerals and requirements for vitamins. Wellbalanced vegetarian diets are able to support normal growth and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 31 publications
1
43
0
2
Order By: Relevance
“…Vegetarian diets are limited in bioavailable iron and so cannot maintain iron balance (Shaw et al, 1995). Other reviews have concluded that vegetarian diets can maintain iron balance if appropriate foods are chosen (Sanders, 1999). Nevertheless, in our study the vegetarian population, especially the vegan, are shown to be potentially at risk of calcium de®ciency (Verger et al, 1999).…”
Section: Discussionmentioning
confidence: 53%
“…Vegetarian diets are limited in bioavailable iron and so cannot maintain iron balance (Shaw et al, 1995). Other reviews have concluded that vegetarian diets can maintain iron balance if appropriate foods are chosen (Sanders, 1999). Nevertheless, in our study the vegetarian population, especially the vegan, are shown to be potentially at risk of calcium de®ciency (Verger et al, 1999).…”
Section: Discussionmentioning
confidence: 53%
“…A substantial population of India adheres to a vegetarian diet for cultural and religious reasons. A vegetarian diet is considered to promote health and longevity by protecting against conditions such as cardiovascular disease (CVD) and cancer [5], however this diet may be deficient in some nutrients [6,7]. In particular a strict vegetarian diet has been associated with increased risk of Cobalamin deficiency [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A vegetarian diet is considered to promote health and longevity by protecting against conditions such as cardiovascular disease (CVD) and cancer [5], however this diet may be deficient in some nutrients [6,7]. In particular a strict vegetarian diet has been associated with increased risk of Cobalamin deficiency [7,8]. Malnutrition is common in India [9] and tropical sprue, gastrointestinal infections, and other nutrient deficiencies frequently result in a malabsorptive state [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is the problem of antibiotics being used as growth promoters for animals kept in intensive farming. This use probably contributes to the emergence of multi-drug-resistant strains of pathogenic bacteria (Sanders 1999). Another problem is that of animal disease epidemics and more serious threat is posed by the chicken flu, as this can lead to possible new influenza epidemics or even pandemics, which can kill millions of people (Webster 2002).…”
Section: Introductionmentioning
confidence: 99%